A tessitura insuspeita: cosmopolitismo, cinema nacional e trajetórias do olhar em Walter Hugo Khouri e Luis Sérgio Person (1960-1968) - Silva, Jaison Castro (2014)
This work aimed to study the cultural cosmopolitan movements in the Brazilian movie industry from 1960 to 1968, which was a period that set forth a field for national cinematography. We firstly performed a historical background showing the cinematographic circles that discussed the intellectual dilemmas in the 1950’s. We next investigated how the demands placed by cinema essayists of the period, mainly after the I Convenção nacional da crítica [1st National Convention on Film Criticism] raised the need of building bridges between the practice and intellectual means of the cinematographic circles. We also investigated the conflicts that sprang from foreign influences on the work of Brazilian filmmakers. The group cinema novo [new cinema] came up parallel to this debate attracting the attention of national and international film analysts. At that same time, Brazilian State and its financial policies focused on the film production that highlighted the cultural importance of this medium. We set forth a cinematographic cosmopolitanism concept specific to that historical background through the layouts of perception that we made taking as depart station the film reviews of that time. In this conceptual frame elaborated from the prior chapters, Walter Hugo Khouri and Luís Sérgio Person were studied through the analysis of their intellectual trajectory and of their films. Both moviemakers made the imaginative engagement across the boundaries as an essential element of their careers. In films as São Paulo sociedade anônima (1965), by Person, and O Corpo Ardente (1966), by Khouri, they expressed dialogues with foreign referentials in an intense way. They dealt with the international style and forms of cinema as a constitutive element of their own practices, intertwining the idiosyncratic time structure to Brazilian culture through their films and cultural practices. Both were reluctant to fit into artistic groups, admitting their works as individual practices of cinema and introducing their unique treatments to technical resources and cinematographic culture. They directed films that make possible routes of perception to the study of visual culture of that time. Their works were inseparable from the cultural diversity in the construction of national cinematographic field, which was remarkable by its plurality of practices.